Children rights: perspectives of different generations - Cordeiro, Leandra (2017)
Introduction: The United Nations General Assembly adopted the Convention on the Rights of the Child- Magna letter for children around the world- On November 20, 1989, and the next year, the document was made oficial as international law. Objectives: The present investigation proposes to analyze and understand the perception of children and adults, ranging from different age groups age on the rights of children and their order of importance. Methods: It is a quantitative study, of exploratory nature. Through a questionnaire of preferred order response, we selected ten rights random from Convention on the Rights of the Child UNICEF, where it was asked, lists that are one to ten, the rights more important, where 1 was the most significant and 10 the less signiicant. There were submitted 151 inquiries, in the age groups between six and sixteen years, referenced, in the stages of psychosocial development proposed by Erikson, from the 4th to the 7th age; Results: it was found that in total (either for children or for adults), it was unanimous that growing up in a healthy family and to have a home it was the most important right. In relation to the least important item, it wasn’t possible to take general conclusions being that the information gathered was very scatter through the different ages. Conclusions: It is essential to give to know and remember the children’s rights both to adults and for children, to open conscience on society, mainly on what it comes to children that are excluded from this essential rights. It is therefore of great importance, emphasize the universality of rights.